Application of high-precision terrestrial light detection and ranging to determine the dislocation geomorphology of Yumen Fault, China - Kang, Shuai; Jiao, Qisong; Ji, Lingyun; Zeng, Yaguang; Chen, Chen (Frontiers in Remote Sensing, 2025)
Ground-based three-dimensional (3D) light detection and ranging (LiDAR) is used to collect high-density point clouds of terrain for high-precision topographic survey, remove information on surface vegetation, and allow for the study of fault rupture. Selected as the study area was the west side of the Yumen Fault in China, characterized by a thrust nappe, and information on this typical fault landform. Fundamental issues such as ground-based 3D LiDAR for field collection, data processing, and 3D fault modeling were then analyzed. Finally, the high-precision topography of the surface rupture in this area was obtained, revealing the typical dextral strike–slip dislocation along the fault zone. In the process of data processing, the iterative closet point (ICP) and the optimal point cloud density were used to improve the high efficiency and precision of data processing. Finally, based on point cloud data processing, a digital elevation model (DEM) with a spatial resolution of 0.1 m was obtained for the study area to classify the geomorphic unit, obtain information on the fault scarp and fault broken gully terrain, and quantitatively study and analyze the horizontal dislocation of gully and displacement distance of the fault scarp. This process revealed several seismic events along the fault zone, accompanied by a typical dextral strike–slip phenomenon.